Evaluation of solvent extracts of selected medicinal plants of Agumbe region for antibacterial activity against plant pathogenic bacteria - K.A. RAVEESHA*, D.L. SHRISHA and (Indian Phytopathology, 2016)
Pseudomonas species are important phytopathogenic bacteria causing diseases in variety of food crops. Developing ecofriendly management practices is necessary to overcome the prohibitive cost and toxic effects of the synthetic antibiotics currently used in the management of plant diseases. Eight plant species collected from Agumbe region of Western Ghats of Karnataka were evaluated for antibacterial activity against plant pathogenic Pseudomonas syringe and Pseudomonas solanacearum. Successive solvent extraction of the test plants was carried out using petroleum ether, chloroform, ethyl acetate and methanol. For antibacterial assay of solvent extract disc diffusion assay was employed. Among eight test plants, Coscinium fenestratum recorded inhibitory activity against Pseudo. syringae. Further, bioautography study (Agar over lay method) revealed the presence of antibacterial active fraction‘s Rf value at 0.32 by clear zone of inhibition. Minimal Inhibitory Concentration of methanol extract of Coscinium fenestratum against Pseudo. syringae was found to be 1.25 mg/ml. Phytochemical analysis revealed the presence of alkaloid as an active component in TLC fraction.